ACC adult corrections in Canada - Weinrath, Michael; Winterdyk, John (De Sitter Publications, 2020)
Introduction to Adult Corrections in Canada / John Winterdyk and Michael Weinrath -- Chapter 1: Adult Corrections within a Canadian Context / John Winterdy and Aja Jacqueline Manning -- Chapter 2: An Historical Overview of Adult Corrections in Canada / John Winterdyk -- Chapter 3: Sentencing and Correctional Sanctions / Derek Spencer -- Chapter 4: Probation and Community Corrections/ Michael Weinrath -- Chapter 5: Prison Life: Doing Time in Canadian Institutions / Rosemary Ricciardelli and Michael Weinrath -- Chapter 6: Women in Custody / Gillian Balfour -- Chapter 7: The Mass Imprisonment of Indigenous Peoples: Canada's Continued Colonial Agenda / Lisa Monchalin and Olga Marques -- Chapter 8: Limiting the State's Right to Punish / Debra Parkes, Kelly Hannah-Moffat and Amy Klassen -- Chapter 9: Offender Assessment, Classification, and Treatment in Canadian Corrections / Claire Goggin, Paul Gendreau, James Bonta, J. Stephen Wormith, Myles Ferguson and Paula Smith -- Chapter 10: Conditional Release in Canada / Tracey Cyca and Tim Williams -- Chapter 11: Adult Restorative Justice in Canada / Andrew Woolford & Amanda Nelund -- Chapter 12: An Introduction to Prison and Penal Abolitionism in Canada / Justin Piché, Kevin Walby and Nicolas Carrier -- Chapter 13: The Future of Corrections in Canada / Rick Ruddell and Katharina Maier.